Unity Technologies: The Story Behind Game Development Industry - Zi Xuan, Yee; Li Chen, Lim; Choon Jin, The (International Journal of Psychosocial Rehabilitation, 2020)
The demand of creative games and high-quality game development engine is increasing throughout the years, especially when gaming industry grow very fast in recent years. This paper shown the abstract timeline of Unity Technologies, where the company start up until year 2019. The founders, David Helgason, Nicholas Francis, and Joachim Ante are inspired to innovate a game development engine for more people to create games easily. Topics reviewed including background, business strategy and key success factors of Unity Technologies. Besides, this case study analyzed its current challenges and provided possible recommendation for Unity Technologies.